2017
DOI: 10.5797/jnet.oa.2016-0087
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategy for Infectious Intracranial Aneurysms in the Era of Interventional Neuroradiology

Abstract: Objective: Aggressive therapeutic intervention is recommended for infectious intracranial aneurysms (IIAs) because they have a higher hemorrhage risk than non-IIAs. In this study, we retrospectively reviewed patients with IIAs treated at our institution and evaluated the contents of treatment and the complications. Results: Endovascular treatment, direct surgery, and conservative management were performed in five, five, and three patients, respectively. In endovascular treatment patients, none developed any he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…2) Many reports suggested that endovascular treatment does not cause complications including infection. 15) The pearl-and-string sign can be a tool for making the diagnosis. Nevertheless, the imaging of both diseases shows various types of aneurysm and it is difficult to make the diagnosis using only imaging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2) Many reports suggested that endovascular treatment does not cause complications including infection. 15) The pearl-and-string sign can be a tool for making the diagnosis. Nevertheless, the imaging of both diseases shows various types of aneurysm and it is difficult to make the diagnosis using only imaging.…”
Section: Discussionmentioning
confidence: 99%
“… 14) Regarding treatment for aneurysms include surgical trapping, clipping, and endovascular coiling and trapping. 1 , 15) Endovascular surgery has become an important treatment for mycotic aneurysm. Many patients with deteriorating conditions and those who have vegetations and require cardiothoracic surgery have been treated with endovascular surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation